Common Discourse Patterns of Cross-diciplinary Research Article Abstracts in English - Tofan Dwi Hardjanto (Humaniora, 2017)
Because of its important role in the advancement of science, attempts have been made to investigate research article abstracts in terms of both their discourse patterning and their linguistic characteristics. This research is an attempt to examine their rhetorical patterning. More specifically, it addresses the questions what common discourse patterns research article abstracts have and whether abstracts from different disciplines show different patterns. The research corpus contained 50 research article abstracts collected from five international journals published in the fields of biology, engineering, linguistics, medicine and physics. The data were analyzed using a four-move abstract structure developed by Hardjanto (1997). The results showed that Moves 1, 3 and 4 were found in most abstracts, and were, therefore, considered as obligatory moves in the abstracts. The most common pattern was found to be a pattern containing all the four moves in the order of 1-2-3-4, especially in abstracts from medicine and linguistics. Another common pattern was a 1-3-4 pattern, found especially in abstracts from biology and physics, whereas abstracts from engineering did not show any preference for a specific pattern even though 40% of them had a 1-2-3-4 pattern. These results suggest that there is a significant disciplinary variation in English research article abstract patterning.